Hydrogels for Tissue Engineering: Addressing Key Design Needs Toward Clinical Translation - Xu, Fei; Dawson, Chloe; Lamb, Makenzie; Mueller, Eva; Stefanek, Evan; Akbari, Mohsen; Hoare, Todd (Frontiers in Bioengineering and Biotechnology, 2022)
While the soft mechanics and tunable cell interactions facilitated by hydrogels have attracted significant interest in the development of functional hydrogel-based tissue engineering scaffolds, translating the many positive results observed in the lab into the clinic remains a slow process. In this review, we address the key design criteria in terms of the materials, crosslinkers, and fabrication techniques useful for fabricating translationally-relevant tissue engineering hydrogels, with particular attention to three emerging fabrication techniques that enable simultaneous scaffold fabrication and cell loading: 3D printing, in situ tissue engineering, and cell electrospinning. In particular, we emphasize strategies for manufacturing tissue engineering hydrogels in which both macroporous scaffold fabrication and cell loading can be conducted in a single manufacturing step – electrospinning, 3D printing, and in situ tissue engineering. We suggest that combining such integrated fabrication approaches with the lessons learned from previously successful translational experiences with other hydrogels represents a promising strategy to accelerate the implementation of hydrogels for tissue engineering in the clinic.